Transformational leadership and its Impact on SMEs Performance in Saudi Arabia - Albihany, Naeem Ali; Balkheer, Bassam Ahmed (The Arab Journal of Administration, 2025)
The study aimed to identify the extent to which SMEs managers adopt transformational leadership style, and to identify the impact of this leadership pattern on the SMEs sector in Makkah. The study began by asking: “What impact has the application of transformational leadership had on the SME sector in Mecca?” The study followed the descriptive methodology for presenting data and information collected through the distribution of a questionnaire targeting the study community. This community is workers in small and medium enterprises sector in Makkah Region including (general managers-department directors-employees), and the number of valid responses was (216). The study’s identification tool consists of several measurements as well as demographic questions: the first was in transformative leadership dimensions (ideal effect - inspirational motivation - mental enlightenment - individual considerations), and the second was the impact of leadership on performance. The study found several findings, most notably a positive impact on the application of transformational leadership to the increased performance of SMEs, as well as a statistical link between the application of transformative leadership in SMEs and increased sales and the ratio of the enterprise’s profits. The study recommended that leaders in enterprises should strengthen transformational leadership in their management of enterprises with the importance of enhancing the role of workers and involving them in decision-making. In addition to raising attention to their development and acquiring new skills to increase the effectiveness of enterprises’ performance.